2010
DOI: 10.1111/j.1365-2427.2009.02322.x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concepts in temporary‐river ecology

Abstract: SUMMARY1. Temporary rivers and streams are among the most common and most hydrologically dynamic freshwater ecosystems. The number of temporary rivers and the severity of flow intermittence may be increasing in regions affected by climatic drying trends or water abstraction. Despite their abundance, temporary rivers have been historically neglected by ecologists. A recent increase in temporary-river research needs to be supported by new models that generate hypotheses and stimulate further research. In this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
693
4
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 603 publications
(720 citation statements)
references
References 194 publications
(329 reference statements)
12
693
4
11
Order By: Relevance
“…Compared to our understanding of perennial stream ecosystems, many important questions remain. Conceptual, empirical, and mechanistic models that may help design and direct future research and test the transferability of results across regions are still lacking (but see Larned et al 2010;Sabater and Tockner 2010). This incomplete understanding of temporary river ecology limits our ability to provide clear management advice for temporary rivers, as the tools needed by water managers (e.g., bioindicators, transferable relationships between flow intermittence and ecosystem processes and patterns) have yet to be developed.…”
Section: Research Perspectives: Gaps and Needs In Temporary River Ecomentioning
confidence: 99%
“…Compared to our understanding of perennial stream ecosystems, many important questions remain. Conceptual, empirical, and mechanistic models that may help design and direct future research and test the transferability of results across regions are still lacking (but see Larned et al 2010;Sabater and Tockner 2010). This incomplete understanding of temporary river ecology limits our ability to provide clear management advice for temporary rivers, as the tools needed by water managers (e.g., bioindicators, transferable relationships between flow intermittence and ecosystem processes and patterns) have yet to be developed.…”
Section: Research Perspectives: Gaps and Needs In Temporary River Ecomentioning
confidence: 99%
“…Because effects on microorganisms increase with drying duration (Langhans and Tockner 2006), changes in fungal activity or assemblage composition favouring more resistant or terrestrial species cannot be excluded. Several studies have shown that the consumption rates of shredders vary according to the fungal species in leaf assemblages (Arsuffi and Suberkropp 1984;Chung and Suberkropp 2009;Jabiol and Chauvet 2012), whereas lower microbial activity during the terrestrial phase (Langhans et al 2008;Larned et al 2010;Bruder et al 2011) might have prevented the degradation of repellent secondary metabolites or more recalcitrant C, such as cellulose, lignin or condensed tannins, resulting in increased leaf toughness and thus, less palatable leaves in the INT than PERM treatments (Irons et al 1988;Hladyz et al 2009;Graça and Cressa 2010;Aßmann et al 2011). As expected, the increased consumption of PERM leaves translated into higher growth rates, which is consistent with the bigger size at eclosion found for an insect detritivore reared on continuously submerged resources (Aspbury and Juliano 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Temporary streams, which exhibit periodical flow interruption, are present in most biomes worldwide (Larned et al 2010). The expected decline in precipitation and higher evapotranspiration rates resulting from increased air temperature will increase drought and likely reduce stream runoff in many regions, including the Mediterranean basin (IPCC 2007) and have already been observed in small catchments in eastern and southern Europe (Stahl et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Larned et al (2010) ressaltam que, devido às mudanças climáticas, o número e a extensão de rios temporários podem aumentar em regiões que enfrentam uma tendência à seca e em regiões onde há a captação de água para o uso socioeconômico.…”
Section: Introductionunclassified